Nasal challenge tests with allergens versus other allergy and rhinitis diagnostic tests - Mazurek, Henryk; Modrzyński, Marek; Krzych-Fałta, Edyta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Consistency of allergen nasal challenge tests with skin prick tests (SPT) and sIgE depends, in particular, on methodological factors and the selection of patients. Positive results of nasal challenge tests with allergens are achieved almost all the time in patients with strongly positive SPT results. The results of conjunctival challenge tests are, in approx. 90% of cases, consistent with the results of nasal challenge tests. In asthma, indications for nasal challenge tests with allergens can be limited to bronchial challenge tests in patients with both asthma and allergic rhinitis, as well as in patients with isolated asthma. In some patients with isolated asthma, negative results of nasal challenge tests may justify considering.